Rehabilitation of reinforced concrete T-joints using GFRP - Swamy, B. Shiva Kumara; Sekar, M. (Journal of Structural Engineering, 2025)
This paper presents an experimental investigation on the behaviour of beam-column joints strengthened and repaired with Glass fiber reinforced polymer (GFRP). The performance of these joints were investigated under cyclic loading and compared with the corresponding unwrapped control beam-column joints. The test specimens were divided into four groups, the first group consisted of beam-column T-joints designed and detailed as per IS: 456-2000, the second group consisted of the joints detailed as per IS: 13920-1993, the third group consisted of tested joints repaired with GFRP and the last group, the joints strengthened before the test by GFRP. The tests were conducted to investigate the effectiveness of GFRP and Isopthalic polyester resin in strengthening reinforced concrete beam-columns joints. On the basis of test results, it was concluded that GFRP wrapping enhances the energy dissipation capacity compared to controlled joints and exhibited sufficient warning time before the ultimate failure. The behaviour of repaired joint was significantly improved and found to be an effective system to repair the damaged joints, also de-bonding dominates the behaviour of external reinforcement unless proper mechanical anchorages are provided.